Detection Coronavirus using Cased-Based Reasoning with Extended Jaccard Coefficient - Murien Nugraheni (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
Coronavirus Disease 2019 or known as COVID-19 is a new disease that can cause respiratory problems and pneumonia. This disease is caused by infection with Severe Acute Respiratory Syndrome Me Coronavirus 2 (SARS-CoV-2). Some of the clinical symptoms that appear vary, ranging from symptoms such as influenza, cough, cold, throat pain, muscle aches, headaches to those with serious complications such as pneumonia or sepsis. This research to build case-based reasoning for early detection of COVID-19 by looking at the characteristics of clinical symptoms seen in a person using the Extended Jaccard Coefficient method. The results show case-based reasoning for early detection of COVID-19 using the Extended Jaccard Coefficient method can model the level of similarity of a new case to an old case.